2019
DOI: 10.3390/rs11050535
|View full text |Cite
|
Sign up to set email alerts
|

Feature Comparison and Optimization for 30-M Winter Wheat Mapping Based on Landsat-8 and Sentinel-2 Data Using Random Forest Algorithm

Abstract: Winter wheat cropland is one of the most important agricultural land-cover types affected by the global climate and human activity. Mapping 30-m winter wheat cropland can provide beneficial reference information that is necessary for understanding food security. To date, machine learning algorithms have become an effective tool for the rapid identification of winter wheat at regional scales. Algorithm implementation is based on constructing and selecting many features, which makes feature set optimization an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…We found that, the maturing phase (10, May-30, June) followed by the reviving phase (20, February-30, March) was particularly crucial for accurate classification of wheat identification. In the maturing period, winter wheat grows rapidly, and the harvested wheat all share the same yellow hue, while other crops are in the early growth phase, which results in higher importance of features derived from the maturing phase [8,17]. Thus, image dates for the maturing phase are the best for extracting winter wheat, and the result of the mono-temporal image composite classification confirmed such a conclusion (Figure 7).…”
Section: The Impact Of Key Crop Development Phases On Classification mentioning
confidence: 65%
See 1 more Smart Citation
“…We found that, the maturing phase (10, May-30, June) followed by the reviving phase (20, February-30, March) was particularly crucial for accurate classification of wheat identification. In the maturing period, winter wheat grows rapidly, and the harvested wheat all share the same yellow hue, while other crops are in the early growth phase, which results in higher importance of features derived from the maturing phase [8,17]. Thus, image dates for the maturing phase are the best for extracting winter wheat, and the result of the mono-temporal image composite classification confirmed such a conclusion (Figure 7).…”
Section: The Impact Of Key Crop Development Phases On Classification mentioning
confidence: 65%
“…These remote sensing datasets provided useful information for studying the spatial distribution and management of land cover and land use (LCLU) at a regional or global scale. However, listed LCLU products were developed mainly for broad LCLU classes (e.g., cropland, forest, and grassland), and few products provide more detailed information about the specific crops [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…With the ability to quickly and efficiently collect information in real time over wide ranges, remote sensing is a rich data source for crop-type mapping [3] . Multiresolution or multitemporal optical images with abundant spectral and texture information have been widely used in crop identification [4][5][6] . However, data acquisition of optical remote sensing images will inevitably be affected by clouds and rain.…”
Section: Introduction mentioning
confidence: 99%
“…When using low-and medium-resolution images as data sources, NDVI and other vegetation indices are typically used as the main features [71]. When higher-resolution remote sensing images are used as data sources, regression methods [72], support vector machines [73,74], random forests [75], linear discriminant analysis [76], and CNNs [77,78] are the more commonly used methods. There is a significant number of mis-segmented pixels at the edges of winter wheat planting areas, which are common problems that these methods must overcome.…”
Section: Introductionmentioning
confidence: 99%